Design Science Research: scientific research linked to artifact design - Pimentel, Mariano (2020)
In Education, we develop artifacts: classes, didactic resources and educational practices. It is possible to interrelate the development of an artifact with the production of theoretical knowledge, and Design Science Research (DSR) is the approach we present on this article, used to do scientific research connected to the development of artifacts. Through this approach, the goal is to design a different reality, modified by artifacts designed to solve problems in given contexts, with the scientific knowledge being the result of the investigation of the use of the artifact in a given situation. DSR is an approach that is still under discussion; in this article, we show how our research group has been appropriating DSR. In particular, we present the DSR Model in which we synthesized the main lessons learned by our group. In order to exemplify the use of the DSR Model, we present the research on Smart Musical Mats. We consider that the DSR Model has been helping make our group’s researches more rigorous in theoretical, epistemological and methodological terms and, thus, more relevant in scientific terms. We present this model because we consider it to be a useful instrument to support other researchers that want to consider and use DSR.